The new intelligent home control system based on the dynamic and intelligent gateway - Jiali Bian; Dengke Fan; Junming Zhang (2011 4th IEEE International Conference on Broadband Network and Multimedia Technology, 2011)
With the emergence of the Internet of Things and improvement of humans' living standards, smart home is becoming the future criterion of home life. Smart home not only gives users a safe, healthy and comfortable living environment, but also allows users to remotely monitor their home state and control home appliances. However, the current smart home systems, including home gateways, wireless sensor network devices and the home networking equipments require constant work. This will not only cause a waste of energy, still can negatively affect the gateway performance. In order to save energy and reduce the cost of smart home, there is a pressing need for a new type of intelligent home control system. This paper presents a new type of intelligent home control system, using Android Phone as a temporary home gateway instead of the default home gateway, thus reducing the constant working hours of the traditional gateway. At the same time, we also construct an intelligent control system based on user behavior analysis, the system will automatically shut down the unused devices by predicting user behavior, so as to achieve energy savings and reduce costs.